DETERMINATION OF RATIONAL PARAMETERS OF THE DRUM MIXER OPERATION BASED ON THE REGRESSION ANALYSIS WHEN OBTANING THE DRY YOGHURT BASE - Borodulin D.M.; Budrik V.G.; Shulbaeva M.T.; Shafrai A.V. (Техника и технология пищевых производств)
In most cases, loose components used in the production of dry yoghurt base have different granular-metric composition and density. Therefore, the development of the effective mixing equipment to obtain dry yoghurt base with a high degree of homogeneity is an actual problem for the dairy industry. To study the intensification of mixing the dry loose materials and to obtain high quality dry yoghurt base, the continuous drum mixer was developed and produced which possesses low energy consumption, mixing efficiency, preservation of the structure of mixed components. In addition, this unit is capable of combined longitudinal and transverse mixing of loose components due to the availability of different loops of the mixture recirculation throughout the length of the drum. The article presents the results of study on identification of the degree of influence of the drum rotation frequency, drum filing coefficient and the location of Г-shaped blades on the quality of dry yoghurt base. Two variants of the location of Г-shaped blades, staggered and helical, have been studied. It has been proved that the best quality of mixture is achieved with the helical arrangement of Г-shaped blades. In this case, it is recommended to mix the ingredients at the drum rotation frequency of 25 rev/min, and the filling coefficient of 20%. Mathematical regression models were obtained because of the processing of the experimental data using the program «Statistica». They predict the quality of dry yoghurt base with a high degree of accuracy. The values of relative error between the experimental and the predicted values of the heterogeneity coefficient are 8.9 and 0.98% for staggered and helical arrangements of Г-shaped blades, respectively.